Cancellation properties in Hall-magnetohydrodynamics with strong guide magnetic field - Martin, Luis Nicolas (2013)
We present a signed measure analysis of compressible Hall-magnetohydrodynamic turbulence with an external guide field. Signed measure analysis allows to characterize the scaling behavior of the sign-oscillating flow structures and their geometrical properties (fractal dimensions of structures). A reduced numerical model, valid when a strong guide magnetic field is present, is used here. In order to discuss the effect of the Hall term, different values for the ion skin depth are considered in the simulations. Results show that as the Hall term is increased the fractal dimension of the current and vorticity sheets decreases. This observation, together with previous analysis of the same fields, provides a comprehensive description of the effect of the Hall force on the formation of structures. Two main processes are identified, namely the widening and unraveling of the sheets.